1921 Wyo. Sess. Laws 101, ch. 83, § 62. - (:unkn) unknown (General Publisher, 1921)
It shall be unlawful for any person to take, kill, wound or destroy any of the game fish of this State by the use of any revolver, pistol, shot gun, rifle or fire arms of any kind or nature.
--
Keywords: FISHING REGULATION